Comparison of the Occupational Stress in Elementary School Teachers of Public and Private Schools in District Bahawalpur - Aisha Muzahir, Sumbal Asghar, Sumera Kanwal (PJDOL, 2022)
Teaching is a stressful job, and the teachers' stress causes psychological and physical strain as a result of being overworked and concerned. This research was done to compare occupational stress among elementary school teachers in public and private schools, as well as to identify sources of occupational stress among elementary school teachers. This research was quantitative in nature, descriptive and cross-sectional study. A questionnaire was used to collect data from the public and private sector elementary school teachers of Bahawalpur district, Pakistan.